(untitled) (Nigerian Journal of Technology, 2009)
Rainfall data from 14 locations in Nigeria (six in the north and eight in the south) were collected for the period spanning 1980 to 2002. The data were subjected to analysis using five different methods of hydrologic forecasting namely: Fuller, Gumbel, Powell, Ven Te Chow and stochastic methods. It was found that Fuller’s method overestimated rainfall magnitude in all locations by a large margin. Powell’s method underestimated rainfall magnitude in all locations studied. Ven Te Chow’s method gave the best prediction in all cases except for Enugu in which case Gumbel’s method was found to be more appropriate. Gumbel’s method closely follows Chow’s method in accuracy for all locations. The analyses show that the maximum 1000 years rainfall is 1100mm and will probably occur in around Calabar. Variations in monthly rainfall magnitude were found to be more in the north and less in the south. It is therefore recommended that the Chow’s method and the Gumbel’s method be adopted for rainfall forecasting in Nigeria.